1979
DOI: 10.1002/eji.1830090803
|View full text |Cite
|
Sign up to set email alerts
|

Studies on T lymphocyte activation II. The target cells for concanavalin A‐induced growth factors

Abstract: Growth factors contained in Con A(concanavalin A)-conditioned media (CM) maintain exponential growth in T cell blasts derived from mitogen stimulation of spleen cells with Con A, phytohemagglutinin, lentil lectin and pokeweed mitogen (PWM), as well as from mixed lymphocyte reactions to H-2D or I-C-encoded determinants and from non-H-2 Mls locus-controlled reactions. Such growth factors are strictly T cell blast-specific, inasmuch as they do not stimulate resting, small T or B lymphocytes nor B cell blasts gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
42
0

Year Published

1979
1979
1986
1986

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 137 publications
(49 citation statements)
references
References 16 publications
7
42
0
Order By: Relevance
“…IL-2 Metabolism. In previous experiments, we (21) and others (22,23) had shown that cells expressing biologically active IL-2-R functioned to remove IL-2 from culture medium in a time-, temperature-, and cell concentration-dependent fashion. Subsequent findings (Cantreli, D. A., and K. A. Smith, manuscript in preparation) have shown that tbe depletion of IL-2 activity from the culture medium is due to a receptor-mediated internalization and degradation of IL-2 molecules that bind to the cells.…”
Section: Il-2-r Expression By T4 + Vs T8 + Cellsmentioning
confidence: 90%
“…IL-2 Metabolism. In previous experiments, we (21) and others (22,23) had shown that cells expressing biologically active IL-2-R functioned to remove IL-2 from culture medium in a time-, temperature-, and cell concentration-dependent fashion. Subsequent findings (Cantreli, D. A., and K. A. Smith, manuscript in preparation) have shown that tbe depletion of IL-2 activity from the culture medium is due to a receptor-mediated internalization and degradation of IL-2 molecules that bind to the cells.…”
Section: Il-2-r Expression By T4 + Vs T8 + Cellsmentioning
confidence: 90%
“…Previous work indicated that T cell growth factor, or IL-2, does not trigger the growth of resting T cells (27,28). Rather, IL-2 acts in conjunction with other signals, or these cells must first be "activated" to respond to IL-2, a process which includes expression of functional receptors (28)(29)(30).…”
mentioning
confidence: 99%
“…It is well established that proliferation of at least some antigen-or mitogen-activated T cells is dependent on T-cell growth factors (TCGF) (16,17). Because TCGF are produced by Lyt-l cells (18), we tested if the enhancement of alloantigen-induced proliferation by aLyt-1 is related to production of TCGF.…”
mentioning
confidence: 99%